Chemically strengthened glass and prediction method of drop failure height thereof, display screen, structural component and electronic device
By establishing the damage resistance characteristic value and optimization process of chemically strengthened glass, the problem of relying on experimental testing for anti-depression performance evaluation in the existing technology is solved, and effective evaluation and improvement of the anti-depression performance of chemically strengthened glass is achieved.
Patent Information
- Application Number
- CN202310073600.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-11
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-01-11
AI Technical Summary
The existing chemically reinforced glass anti-depressive performance evaluation methods rely on destructive experimental testing and cannot provide improvement guidance. The anti-depressive performance is affected by many factors and is difficult to predict.
By establishing the damage resistance characteristic value of chemically reinforced glass, meeting specific compressive stress layer thickness and elastic performance indicators, it predicts its drop failure height, and optimizes the material formula and strengthening process of raw glass.
It has achieved effective evaluation of the resistance of chemically strengthened glass without destroying the glass, and improved the resistance to decline to above 1.8m through optimized processes, meeting the needs in most scenarios.
Smart Images

Figure CN116143422B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass, and in particular to a chemically strengthened glass and a prediction method for its drop failure height, a display screen, a structural component and an electronic device. Background Art
[0002] Glass has excellent optical, chemical and processability properties. As a screen cover, it has been widely used in mobile electronic consumer products represented by mobile phones. However, due to the high brittleness of glass and its low resistance to crack propagation, the tiny cracks introduced during the preparation, processing and use process are prone to rapid expansion under the action of external forces, eventually leading to fracture failure. Therefore, electronic products with glass cover plates are prone to breakage in collisions, falls and other scenarios, resulting in damage to the appearance, reduced or even lost working performance, causing losses to consumers and reducing user experience. In other words, drop resistance and drop resistance have evolved into the core needs of consumers for mobile electronic products. At present, the drop resistance of glass cover plates can be improved by chemical strengthening methods. However, since the final drop resistance of chemically strengthened glass is affected by the various properties of chemically strengthened glass, the existing evaluation methods generally test the drop resistance of chemically strengthened glass through destructive experiments. After the test is completed, it can only be obtained whether the drop resistance height of the glass meets the requirements, which has no guiding significance for how to further improve the drop resistance of the glass. Summary of the invention
[0003] The present application provides a chemically strengthened glass and a prediction method for its drop failure height, a display screen, a structural component and an electronic device, so as to effectively evaluate the drop resistance of the chemically strengthened glass without destroying the chemically strengthened glass.
[0004] In a first aspect, the present application provides a chemically strengthened glass, wherein the chemically strengthened glass is obtained by chemically strengthening raw glass, and the damage resistance characteristic value of the chemically strengthened glass is satisfy and Satisfying formula (1):
[0005]
[0006] SCE 50 is the total compressive stress elastic energy from 50 μm depth to the compressive stress layer thickness (DOL) of the chemically strengthened glass, where SCE 50 Satisfying formula (2):
[0007]
[0008] In formula (1) and formula (2), K IC is the fracture toughness of the raw glass;
[0009] v is the Poisson's ratio of the raw glass;
[0010] E is the Young's modulus of the raw glass;
[0011] T is the thickness of the chemically strengthened glass;
[0012] T max is a constant, and its value is 0.75mm;
[0013] σ c (x) is the compressive stress of the chemically strengthened glass at a depth x.
[0014] The chemically strengthened glass of the present application is prepared by combining the fracture toughness of the raw glass, the Poisson's ratio of the raw glass, the Young's modulus of the raw glass, the thickness of the chemically strengthened glass, the compressive stress of the chemically strengthened glass, and the SCE of the chemically strengthened glass. 50 Establishing a relationship to obtain the damage resistance characteristic value of chemically strengthened glass The damage resistance characteristic value of chemically strengthened glass Control The drop resistance height of the chemically strengthened glass can be increased to more than 1.1m, and can basically reach more than 1.8m. The drop resistance height of some chemically strengthened glass can reach 2.1m. The damage resistance characteristic value of the chemically strengthened glass in this application can help quantify the intrinsic relationship between the drop resistance level of the chemically strengthened glass and the material-level performance of the glass raw materials and the strengthening stress level, and guide the improvement of the material formula of the raw glass and the optimization of the strengthening process to obtain chemically strengthened glass with better drop resistance.
[0015] In a possible implementation, the Young's modulus E of the raw glass satisfies: 75≤E≤120GPa. The fracture toughness K of the raw glass IC Satisfy: 0.7≤K IC ≤0.9MPa·m 0.5 The shear modulus G of the raw glass is: 30≤G≤50GPa. The Vickers hardness HV of the raw glass satisfies: 500≤HV≤900kgf / mm 2 The brittleness coefficient m of the raw glass satisfies: 24≤m≤45. The glass transition temperature T of the raw glass g Satisfy: 520≤T g ≤750℃.
[0016] In a possible implementation, the SCE of the chemically strengthened glass 50 Satisfy: 4.5 ≤ SCE 50 ≤9MPa·m 0.5. The surface compressive stress CS of the chemically strengthened glass satisfies: 400≤CS≤1500MPa. The compressive stress CS50 at 50μm of the chemically strengthened glass satisfies: 80≤CS50≤220MPa. The average tensile stress CT.av of the tensile stress zone of the chemically strengthened glass satisfies: 60≤CT.av≤110MPa. The compressive stress layer thickness DOL of the chemically strengthened glass is ≤0.2Tμm. The thickness T of the chemically strengthened glass is ≤1mm. The Vickers hardness HV1 of the chemically strengthened glass satisfies: 500≤HV1≤900kgf / mm 2 .
[0017] In a possible implementation, the raw glass includes the following components in terms of mole percentage:
[0018] SiO2: 45~59.5%, Al2O3: 9~30%, MgO: 7~30%, La2O3: 0~8%, ZrO2: 0~10%, ZnO: 0~5%, Li2O: 5.5~15%, Na2O: 1~5%, K2O: 2~5%.
[0019] In a possible implementation, the chemical strengthening includes at least one ion exchange treatment, each ion exchange treatment time is 0.3-10 hours, and each ion exchange temperature is 360-500°C.
[0020] In a possible implementation, the drop failure height of the chemically strengthened glass is greater than or equal to 1.1 m, and may further be greater than or equal to 2 m.
[0021] Among them, the data in the above-mentioned possible implementation methods of the present application, such as the fracture toughness of the raw glass, the Poisson's ratio of the raw glass, the Young's modulus of the raw glass, the thickness of the chemically strengthened glass, the compressive stress of the chemically strengthened glass, etc., when measuring, the values within the scope of engineering measurement error should be understood to be within the scope specified in the present application.
[0022] In a second aspect, the present application provides a chemically strengthened glass, wherein the chemically strengthened glass is obtained by chemically strengthening raw glass, and the raw glass comprises the following components:
[0023] SiO2: 45~59.5%, Al2O3: 9~30%, MgO: 7~30%, La2O3: 0~8%, ZrO2: 0~10%, ZnO: 0~5%, Li2O: 5.5~15%, Na2O: 1~5%, K2O: 2~5%.
[0024] In a possible implementation, the shear modulus G of the raw glass satisfies: 30≤G≤50GPa. The Vickers hardness HV of the raw glass satisfies: 500≤HV≤900kgf / mm2 The brittleness coefficient m of the raw glass satisfies: 24≤m≤45. The glass transition temperature T of the raw glass g Satisfy: 520≤T g ≤750℃.
[0025] In a third aspect, the present application provides a method for predicting the drop failure height of chemically strengthened glass. According to the damage resistance characteristic value of the chemically strengthened glass described in the present application, Predicting the drop failure height H of the chemically strengthened glass, wherein H is related to Positive linear correlation.
[0026] In a fourth aspect, the present application provides a display screen comprising the chemically strengthened glass of the present application.
[0027] In a fifth aspect, the present application provides a structural component, including the chemically strengthened glass described in the present application. In addition to the chemically strengthened glass, the structural component of the present application may also include a packaging frame, a packaging shell, and other components for fixing the chemically strengthened glass.
[0028] In a sixth aspect, the present application also provides an electronic device, including the display screen of the present application or the structural component of the present application.
[0029] The technical effects that can be achieved by the second to sixth aspects mentioned above can be described with reference to the corresponding effects in the first aspect mentioned above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The CS50 variation curves of the chemically strengthened glass of the embodiment of the present application and the comparative example at different temperatures and times;
[0031] Figure 2 The CT.av variation curves of the chemically strengthened glass of the embodiment and the comparative example of the present application at different temperatures and times;
[0032] Figure 3 For different embodiments Comparison chart of A value and H value. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.
[0034] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.
[0035] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.
[0036] Existing chemically strengthened glass is strengthened by a single ion exchange (Li + -Na + ) and secondary ion exchange strengthening (Na + -K + ), its surface compressive stress (compressive stress at surface, CS) can reach 800MPa, the compressive stress at a depth of 50μm from the surface (compressive stress at 50μm depth, CS50) can be close to 100MPa, and the thickness of the compressive stress layer (depth of compressive layer, DOL) can exceed 110μm. Applying this type of chemically strengthened glass as a cover plate to mobile electronic products such as mobile phones can effectively improve the product's drop resistance and anti-drop performance. For example, in a representative drop scenario (such as sandpaper surface), the drop height of the mobile phone can be increased from 0.4m to 0.8m. Due to the large number of factors affecting the drop resistance of chemically strengthened glass, the existing methods are unable to predict its drop resistance based on the parameters of the chemically strengthened glass itself, and destructive testing experiments are required to obtain it.
[0037] In view of this, the present application provides a chemically strengthened glass, wherein the chemically strengthened glass is obtained by chemically strengthening raw glass, and the damage resistance characteristic value of the chemically strengthened glass is satisfy and Satisfying formula (1):
[0038]
[0039] SCE 50 is the compressive stress elastic energy from the depth of 50 μm of the chemically strengthened glass to the thickness DOL of the compressive stress layer of the chemically strengthened glass, SCE 50 The unit is Pa·m, where SCE 50 Satisfying formula (2):
[0040]
[0041] In formula (1) and formula (2), K IC is the fracture toughness of the raw glass, in MPa·m 0.5 ;
[0042] v is the Poisson's ratio of the raw glass;
[0043] E is the Young's modulus of the raw glass, in GPa;
[0044] T is the thickness of the chemically strengthened glass, in mm;
[0045] T max is a constant, and its value is 0.75mm;
[0046] σ c (x) is the compressive stress of the chemically strengthened glass at a depth x, in MPa, wherein the depth x has a value range of 50 μm-compressive stress layer thickness DOL.
[0047] The chemically strengthened glass applied for can be produced according to Adjust the various properties of raw glass, quantify the constitutive relationship between the drop resistance and fall resistance level and the material-level performance of raw glass, guide the improvement of raw glass material formula and strengthening process, design new formula and strengthening process with excellent drop resistance, so as to obtain chemically strengthened glass with better drop resistance and fall resistance. Through experimental verification, chemically strengthened glass that meets the conditions specified in this application has excellent drop resistance. In specific scenarios, the drop failure height of the whole machine is further increased from 1.0m to 1.8m, and the highest even exceeds 2.1m, which meets the drop resistance performance requirements in most scenarios.
[0048] Among them, in order to make the chemically strengthened glass have a higher damage resistance characteristic value This can be achieved by improving the intrinsic mechanical properties of the raw glass, such as K IC , E, v; it can also be achieved by increasing the stress characteristic value of the raw glass after strengthening, such as SCE 50The optimization of the above stress characteristic values further requires that the dynamic properties of the raw glass, such as the diffusion coefficient D and the relaxation time τ, meet specific requirements in order to adjust and optimize the intrinsic mechanical properties and thermodynamic properties of the raw glass.
[0049] In the chemically strengthened glass of the embodiment of the present application, the damage resistance characteristic value of the chemically strengthened glass is The range is 1.3-1.7. When the value is lower than 1.3, the drop resistance is limited and cannot meet the product reliability requirements. When the value is higher than 1.7, the glass has poor glass-forming properties, is difficult to mass produce, and has low commercial application possibilities. The value of is limited to the range of 1.3-1.7, which can effectively ensure that the chemically strengthened glass has high drop resistance and commercial application potential. As an example, The value of can be, for example, 1.3, 1.4, 1.5, 1.6 or 1.7.
[0050] In an optional embodiment, the Young's modulus E of the raw glass satisfies: 75≤E≤120GPa. A high Young's modulus is beneficial to ensuring the stiffness and strength of the chemically strengthened glass on the one hand, and is also beneficial to obtaining a high compressive stress value after chemical strengthening on the other hand, which can help improve the drop resistance and fall resistance of the chemically strengthened glass.
[0051] Illustratively, the Young's modulus E of the raw glass may be 75 GPa, 80 GPa, 85 GPa, 90 GPa, 95 GPa, 100 GPa, 105 GPa, 110 GPa, 115 GPa or 120 GPa.
[0052] The fracture toughness K of the raw glass IC Satisfy: 0.7≤K IC ≤0.9MPa·m 0.5 High fracture toughness not only improves the intrinsic damage resistance of raw glass, but also improves the resistance of raw glass to crack propagation and bifurcation, which helps to improve the tensile stress limit of chemically strengthened glass, and thus helps to improve the drop resistance and shatter resistance of chemically strengthened glass.
[0053] For example, the fracture toughness K of the raw glass IC For example, it can be 0.7 MPa·m 0.5 、0.72MPa·m 0.5 、0.74MPa·m 0.5 、0.76MPa·m 0.5 、0.78MPa·m 0.5 , 0.8MPa·m 0.5 、0.82MPa·m0.5 、0.84MPa·m 0.5 、0.86MPa·m 0.5 、0.88MPa·m 0.5 or 0.9MPa·m 0.5 .
[0054] The shear modulus G of the raw glass satisfies: 30≤G≤50GPa. A high shear modulus G can help improve the structural rigidity of the chemically strengthened glass and ensure its shape and dimensional accuracy. Exemplarily, the shear modulus G of the raw glass can be, for example, 30GPa, 32GPa, 34GPa, 36GPa, 38GPa, 40GPa, 42GPa, 44GPa, 46GPa, 48GPa or 50GPa.
[0055] The Vickers hardness HV1 of the raw glass meets the following requirements: 500≤HV1≤900kgf / mm 2 A high Vickers hardness HV1 can help improve the wear resistance and scratch resistance of chemically strengthened glass. For example, the Vickers hardness HV1 of the raw glass can be 500 kgf / mm 2 、550kgf / mm 2 、600kgf / mm 2 、650kgf / mm 2 、700kgf / mm 2 、750kgf / mm 2 、800kgf / mm 2 、850kgf / mm 2 or 900kgf / mm 2 .
[0056] The brittleness coefficient m of the raw glass satisfies: 24≤m≤45. Exemplarily, the brittleness coefficient m of the raw glass may be, for example, 24, 27, 30, 33, 36, 39, 42 or 45. The brittleness coefficient within this range ensures that the raw glass has a wide thermal processing window and has mass production potential.
[0057] In one embodiment, the SCE of chemically strengthened glass 50 Satisfy: 4.5 ≤ SCE 50 ≤9MPa·m 0.5 High SCE 50 Can effectively improve Improve the drop resistance of chemically strengthened glass.
[0058] The surface compressive stress CS of the chemically strengthened glass satisfies: 400≤CS≤1500MPa. High surface compressive stress CS can effectively inhibit the initiation and expansion of surface defects of the chemically strengthened glass and improve the damage resistance of the chemically strengthened glass. Exemplarily, the surface compressive stress CS of the chemically strengthened glass can be 400MPa, 500MPa, 600MPa, 700MPa, 800MPa, 900MPa, 1000MPa, 1100MPa, 1200MPa, 1300MPa or 1400MPa.
[0059] The compressive stress CS50 of the chemically strengthened glass at 50 μm satisfies: 80≤CS50≤220 MPa. High CS50 can effectively improve SCE 50 , increase the sharp contact penetration resistance, and improve the drop resistance of chemically strengthened glass on rough ground. Exemplarily, the compressive stress CS50 of the chemically strengthened glass at 50 μm may be 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa, 210 MPa or 220 MPa.
[0060] The thickness of the compressive layer (DOL) of the chemically strengthened glass is ≤0.2Tμm. A high DOL can increase SCE 50 , which helps to make chemically strengthened glass obtain higher
[0061] The average tensile stress at central region (CT.av) of the chemically strengthened glass satisfies: 60≤CT.av≤110MPa. The tensile and compressive stresses of the chemically strengthened glass are in equilibrium, and the tensile stress in this range can ensure that the compressive stress is in an appropriate range. Exemplarily, the value of CT.av can be, for example, 60MPa, 62MPa, 65MPa, 68MPa, 70MPa, 75MPa, 80MPa, 85MPa, 88MPa, 90MPa, 92MPa, 95MPa, 100MPa, 105MPa or 110MPa. Wherein, the thickness of the chemically strengthened glass is T≤1mm.
[0062] The Vickers hardness HV2 of chemically strengthened glass meets the following requirements: 500≤HV2≤900kgf / mm 2 For example, the Vickers hardness HV2 of chemically strengthened glass may be 500 kgf / mm 2 、550kgf / mm 2、600kgf / mm 2 、650kgf / mm 2 、700kgf / mm 2 、750kgf / mm 2 、800kgf / mm 2 、850kgf / mm 2 or 900kgf / mm 2 .
[0063] In an optional embodiment, the raw glass for forming the chemically strengthened glass includes the following components, measured by mole percentage: SiO2: 45-59.5%, Al2O3: 9-30%, MgO: 7-30%, La2O3: 0-8%, ZrO2: 0-10%, ZnO: 0-5%, Li2O: 5.5-15%, Na2O: 1-5%, and K2O: 2-5%.
[0064] Wherein, as an exemplary illustration, in the raw glass, the molar proportion of SiO2 may be, for example, 45%, 46%, 47%, 48%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59% or 59.5%. The molar proportion of Al2O3 may be, for example, 9%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%. The molar proportion of MgO may be, for example, 7%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%. The molar proportion of La2O3 may be, for example, 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%. The molar proportion of ZrO2 may be, for example, 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. The molar proportion of ZnO may be, for example, 0%, 1%, 2%, 3%, 4% or 5%. The molar proportion of Li2O may be, for example, 5.5%, 6%, 7%, 8%, 10%, 11%, 12%, 13%, 14% or 15%. The molar proportion of Na2O may be, for example, 1%, 2%, 3%, 4% or 5%. The molar proportion of K2O may be, for example, 2%, 3%, 4% or 5%.
[0065] Wherein, the chemical strengthening includes at least one ion exchange treatment, each ion exchange treatment time is 0.3-10h, and each ion exchange temperature is 360-500°C.
[0066] As an exemplary illustration, chemical strengthening may include the following steps: subjecting the raw glass to a temperature slightly below T gPreheat treatment is carried out at a temperature of 100°C for 2-4 hours; then the heat-treated raw glass is placed in a salt bath and kept warm for 10-200 minutes. The salt bath is a pure salt or a mixed salt bath of potassium nitrate and sodium nitrate. The chemical strengthening of the embodiment of the present application may include two ion exchanges. When the first ion exchange is carried out, the main component of the salt bath is sodium nitrate, and the minimum content must be higher than the molar ratio of Na2O / (Li2O+Na2O+K2O) in the raw glass component; when the second ion exchange is carried out, the main component of the salt bath is potassium nitrate, and the minimum content must be higher than the molar ratio of Na2O / (Li2O+Na2O+K2O) in the raw glass component.
[0067] Through the above-mentioned chemical strengthening process, ion diffusion can be fully carried out, and stress relaxation phenomenon can be suppressed to a great extent, and finally chemically strengthened glass with high pressure stress is obtained.
[0068] Based on the same technical concept, an embodiment of the present application provides a chemically strengthened glass, which is obtained by chemically strengthening raw glass, wherein the raw glass includes the following components: SiO2: 45-59.5%, Al2O3: 9-30%, MgO: 7-30%, La2O3: 0-8%, ZrO2: 0-10%, ZnO: 0-5%, Li2O: 5.5-15%, Na2O: 1-5%, and K2O: 2-5%.
[0069] The shear modulus G of the raw glass satisfies: 30≤G≤50GPa. A high shear modulus G can help improve the structural rigidity of the chemically strengthened glass and ensure its shape and dimensional accuracy. Exemplarily, the shear modulus G of the raw glass can be, for example, 30GPa, 32GPa, 34GPa, 36GPa, 38GPa, 40GPa, 42GPa, 44GPa, 46GPa, 48GPa or 50GPa.
[0070] The Vickers hardness HV1 of the raw glass meets the following requirements: 500≤HV1≤900kgf / mm 2 A high Vickers hardness HV1 can help improve the wear resistance and scratch resistance of chemically strengthened glass. For example, the Vickers hardness HV of the raw glass can be 500 kgf / mm 2 、550kgf / mm 2 、600kgf / mm 2 、650kgf / mm 2 、700kgf / mm 2 、750kgf / mm 2 、800kgf / mm 2 、850kgf / mm 2 or 900kgf / mm 2 .
[0071] The brittleness coefficient m of the raw glass satisfies: 24≤m≤45. Exemplarily, the brittleness coefficient m of the raw glass may be, for example, 24, 27, 30, 33, 36, 39, 42 or 45. The brittleness coefficient within this range ensures that the raw glass has a wide thermal processing window and has mass production potential.
[0072] The chemically strengthened glass obtained by using the components of the embodiments of the present application has SiO2 as its main network component. Alkali metal ions such as Li2O, Na2O and K2O are important carriers for chemical strengthening and introduction of compressive stress; however, they will also introduce non-bridging oxygen, destroying the network structure and strength of the quartz glass, resulting in a decrease in elastic modulus and fracture toughness. In order to compensate for the loss of intrinsic mechanical properties of the raw glass, Al2O3, ZrO2, La2O3, MgO and ZnO can be introduced to improve the strength and integrity of the network structure of the raw glass, thereby obtaining a high elastic modulus and fracture toughness, and also suppressing the stress relaxation effect of the glass during the strengthening process, thereby obtaining a chemically strengthened glass with high drop resistance.
[0073] In addition, the damage resistance characteristic value of the chemically strengthened glass of the embodiment of the present application is satisfy and Satisfying formula (1): Then according to The value of adjusts the chemical strengthening process of the raw glass so that it cooperates with the components of the raw glass to obtain a specific value Chemically strengthened glass.
[0074] The damage resistance characteristic value of the chemically strengthened glass of the embodiment of the present application is The drop failure height of chemically strengthened glass can be effectively predicted. Among them, the drop failure height H of chemically strengthened glass is related to the damage resistance characteristic value Linear positive correlation.
[0075] Based on the same technical concept, the embodiment of the present application further provides a display screen, which may include the chemically strengthened glass of the embodiment of the present application as a glass cover plate to improve the drop resistance of the display screen.
[0076] Based on the same technical concept, the embodiment of the present application further provides a structural member, which includes the chemically strengthened glass of the embodiment of the present application and may include a frame for fixing the chemically strengthened glass.
[0077] Based on the same technical concept, an embodiment of the present application further provides an electronic device, which includes the display screen of the embodiment of the present application.
[0078] The properties of the chemically strengthened glass of the present application will be further described in detail below in conjunction with specific examples and comparative examples.
[0079] The test methods used in the following examples and comparative examples are described here.
[0080] Based on the sound velocity method, a pulse echo spectrometer was used to test the Young's modulus, shear modulus and Poisson's ratio of the raw glass.
[0081] The Vickers hardness of the raw glass was tested using a hardness tester under a load of 50 g.
[0082] The fracture toughness of the raw glass was tested using a universal testing machine. The glass transition temperature T of the raw glass was measured using a differential scanning calorimeter (Mettler DSC3+). g .
[0083] Based on the national standard “Test method for high temperature viscosity of ultra-thin glass melt”, the high temperature viscosity of the raw glass was tested using a high temperature viscometer, and the brittle coefficient m of the raw glass was obtained based on VFT model fitting.
[0084] The characteristic stress values of chemically strengthened glass were tested using scattered light glass stress meter (such as SLP2000) and surface stress meter (such as FSM6000). FSM6000 is used to test the surface compressive stress CS, and SLP2000 is used to test the compressive stress values of chemically strengthened glass at different depths, such as the compressive stress CS50 at 50μm, the thickness of the compressive stress layer DOL, and the average tensile stress CT.av in the tensile stress zone, where SCE 50 Compressive stress σ obtained by SLP2000 test c The (x) curve is obtained by integrating equation (2).
[0085] In order to test the drop resistance and fall resistance of the chemically strengthened glass of different embodiments and comparative examples under rough surfaces, the obtained chemically strengthened glass was assembled in a commercial mobile phone, and the failure height of the controlled drop on the surface of 180 mesh SiC sandpaper was tested using a drop machine. The initial drop height was 0.6m, and gradually increased to 2.5m in steps of 0.1m. The failure height was the height H when the glass screen was broken. In order to obtain the average value of the failure height of the cover glass of the embodiments and comparative examples, at least 5 pieces of cover glass were selected for 5 drop tests.
[0086] Raw glass preparation
[0087] Examples 1-15
[0088] Examples 1-15 are respectively a raw glass, wherein the components of the raw glass of each example are listed in Table 1 respectively.
[0089] Table 1
[0090]
[0091] Table 1 (continued)
[0092]
[0093]
[0094] In Table 1, the preparation process of each raw glass is as follows: accurately weigh according to the ratio in Table 1, and mix thoroughly, melt at a high temperature of 1600-1680℃ for 2-8h, obtain a uniform glass liquid and cast it into an iron mold to obtain a glass brick; then, g The glass bricks are subjected to stress relief annealing at a temperature of 30-70°C for 24-48 hours, and then gradually cooled to room temperature to obtain glass bricks in an almost stress-free state. The glass bricks are subjected to multiple processes such as multi-wire cutting, rough grinding, CNC, and polishing to obtain raw glass of appropriate size.
[0095] The raw glass obtained in each embodiment was tested for performance, and the test results can be found in Table 1. As can be seen from Table 1, the raw glass of the embodiments of the present application has a Young's modulus greater than 85 GPa, and in some measured examples the Young's modulus is close to 100 GPa, and in some measured examples the Young's modulus is even close to 110 GPa; a high Young's modulus is beneficial to ensuring the rigidity and strength of the mobile phone cover on the one hand, and on the other hand it is also beneficial to obtaining a high compressive stress value after chemical strengthening. In terms of fracture toughness, the raw glass of some measured examples has a fracture toughness higher than 0.75 MPa·m 0.5 , some measured cases are higher than 0.8MPa·m 0.5 , some measured fracture toughness is close to 0.85MPa·m 0.5 High fracture toughness not only improves the intrinsic damage resistance of raw glass, but also improves the resistance of raw glass to crack propagation and bifurcation, thereby helping to improve the tensile stress limit of chemically strengthened glass.
[0096] In addition, the raw glass of the present application also has excellent scratch resistance and wear resistance. Under a load of 50g, the Vickers hardness of some measured examples is generally higher than 550kgf / mm 2 , the maximum can exceed 800kgf / mm 2 .
[0097] In addition, the raw glass of the present application also has excellent mass production potential. g Between 550-750℃, the brittleness coefficient m is between 24-45, which is suitable for various preparation processes such as melting method, overflow method, float method, calendering method, etc.
[0098] Chemical strengthening treatment
[0099] The raw glass corresponding to Examples 1, 3, 4, and 10 is subjected to chemical strengthening treatment. The strengthening process used in the chemical strengthening treatment includes two ion exchange treatments, specifically including the following steps: g Preheat treatment is carried out at a temperature of 100°C for 2-4 hours; then the heat-treated raw glass is placed in a salt bath and kept warm for 10-480 minutes. The salt bath is a pure salt or a mixed salt bath of potassium nitrate and sodium nitrate. The chemical strengthening of the embodiment of the present application may include two ion exchanges. When the first ion exchange is carried out, the main component of the salt bath is sodium nitrate, and the minimum content must be higher than the molar ratio of Na2O / (Li2O+Na2O+K2O) in the raw glass component; when the second ion exchange is carried out, the main component of the salt bath is potassium nitrate, and the minimum content must be higher than the molar ratio of Na2O / (Li2O+Na2O+K2O) in the raw glass component.
[0100] The specific chemical strengthening processes and stress characteristic values of the raw glass of Examples 1, 3, 4, and 10 are listed in Table 2. Comparative Example 1 is a commercially available raw glass.
[0101] Table 2
[0102]
[0103]
[0104] As shown in Table 2, taking CS as an example, in some measured cases, CS exceeds 0.8 GPa, reaches 1.0 GPa, and even exceeds 1.4 GPa. Taking CS50 as an example, the CS50 of chemically strengthened glass in Table 3 generally exceeds 160 MPa, and in some measured cases, it even exceeds 180 MPa, and the highest reaches 220 MPa. At the same time, DOL is generally higher than 13% of the original glass thickness.
[0105] In addition, the CS50 and CT.av curves of the chemically strengthened glasses corresponding to Examples 1 and 4 and Comparative Example 1 at different temperatures and different times were tested respectively. The test results are shown in FIG. Figure 1 and Figure 2 As shown. Among them, Figure 1 (a) is the CS50 variation curve of the chemically strengthened glass corresponding to Example 1 at different temperatures and different times. Figure 1 (b) is the CS50 variation curve of the chemically strengthened glass corresponding to Example 4 at different temperatures and different times. Figure 1 (c) is the CS50 variation curve of the chemically strengthened glass corresponding to Comparative Example 1 at different temperatures and different times. Figure 2 (a) is the CT.av variation curve of the chemically strengthened glass corresponding to Example 1 at different temperatures and different times. Figure 2(b) is the CT.av variation curve of the chemically strengthened glass corresponding to Example 4 at different temperatures and different times. Figure 2 (c) is the CS50 variation curve of the chemically strengthened glass corresponding to Comparative Example 1 at different temperatures and different times.
[0106] Combination Figure 1 and Figure 2 As shown, at 380-460℃, Li + -Na + After 0-8 hours of exchange, the compressive stress continued to increase, and no stress relaxation was observed. Taking the strengthening temperature of 460℃ as an example, the strengthening time was extended from 20 minutes to 8 hours. Figure 1 As shown, compared with Comparative Example 1, CS50 of Examples 1 and 4 of the present application increased monotonically from 40 MPa to about 180 MPa. Figure 2 As shown, compared with Comparative Example 1, CT.av of Examples 1 and 4 of the present application increases monotonically from about 20 MPa to about 80 MPa. It can be seen that the chemically strengthened glass of the examples of the present application has very excellent stress relaxation resistance, a wide ion exchange process window, and a very high compressive stress can be obtained under the ion exchange process.
[0107] Examples 16-19 and Comparative Examples 2-9
[0108] Examples 16-19 and Comparative Examples 2-9 are chemically strengthened glasses, respectively, and their corresponding performance parameters are listed in Table 3. The chemically strengthened glasses of Examples 16-19 are homemade chemically strengthened glasses, and the chemically strengthened glasses of Comparative Examples 2-9 are commercially available chemically strengthened glasses.
[0109] Table 3
[0110]
[0111]
[0112] It can be seen from the relevant data in Table 3 that when each embodiment is within the range specified in the present application, after testing, the corresponding failure height of the chemically strengthened glass of each embodiment is higher than that of the comparative examples 2-9. The average failure height of the chemically strengthened glass drop test in each measured example generally exceeds 1.8m, and even when dropped from a height of 2.5m, the cover glass still maintains its structural integrity, showing outstanding drop resistance. The value of is outside the range specified in this application, and its corresponding failure height is also low. Therefore, the chemically strengthened glass that meets the various performance parameters of the embodiment of this application has excellent drop resistance. At the same time, it can also be based on the range specified in the embodiment of this application. The value can effectively predict the failure height of chemically strengthened glass. The value of can be used to adjust the formula of raw glass and process conditions in a targeted manner so that the chemically strengthened glass can meet the drop resistance requirements.
[0113] in addition, Figure 3 For different embodiments Comparison chart of value and H value. Figure 3 It can be seen that with With the increase of the value, the failure height of the chemically strengthened glass drop test in each measured example generally increases gradually.
[0114] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A chemically strengthened glass, characterized in that: The chemically strengthened glass is obtained by ion exchange process from raw glass, and the damage resistance characteristic value of the chemically strengthened glass is satisfy and Satisfying formula (1): SCE 50 is the total compressive elastic energy of the chemically strengthened glass from 50 μm depth to the depth of compressive layer (DOL), where SCE 50 Satisfying formula (2): In formula (1) and formula (2), K IC is the fracture toughness of the raw glass; v is the Poisson's ratio of the raw glass; E is the Young's modulus of the raw glass; T is the thickness of the chemically strengthened glass; T max is a constant, and its value is 0.75mm; σ c (x) is the compressive stress of the chemically strengthened glass at a depth x.
2. The chemically strengthened glass according to claim 1, wherein: The Young's modulus E of the raw glass satisfies: 75≤E≤120GPa.
3. The chemically strengthened glass according to claim 1 or 2, characterized in that: The fracture toughness K of the raw glass IC Satisfy: 0.7≤K IC ≤0.9MPa·m 0.5 .
4. The chemically strengthened glass according to any one of claims 1 to 3, characterized in that: The shear modulus G of the raw glass satisfies: 30≤G≤50GPa.
5. The chemically strengthened glass according to any one of claims 1 to 4, characterized in that: The Vickers hardness HV1 of the raw glass satisfies: 500≤HV1≤900kgf / mm 2 .
6. The chemically strengthened glass according to any one of claims 1 to 5, characterized in that: The brittleness coefficient m of the raw glass satisfies: 24≤m≤45.
7. The chemically strengthened glass according to any one of claims 1 to 6, characterized in that: The glass transition temperature T of the raw glass g Satisfy: 520≤T g ≤750℃.
8. The chemically strengthened glass according to any one of claims 1 to 7, characterized in that: SCE of the chemically strengthened glass 50 Satisfy: 4.5 ≤ SCE 50 ≤9Pa·m.
9. The chemically strengthened glass according to any one of claims 1 to 8, characterized in that: The surface compressive stress CS of the chemically strengthened glass satisfies: 400≤CS≤1500MPa.
10. The chemically strengthened glass according to any one of claims 1 to 9, characterized in that: The compressive stress CS50 of the chemically strengthened glass at 50 μm satisfies: 80≤CS50≤220 MPa.
11. The chemically strengthened glass according to any one of claims 1 to 10, characterized in that: The compressive stress layer thickness DOL of the chemically strengthened glass is ≤0.2T μm.
12. The chemically strengthened glass according to any one of claims 1 to 11, characterized in that: The average tensile stress CT.av of the tensile stress zone of the chemically strengthened glass satisfies: 60≤CT.av≤110MPa.
13. The chemically strengthened glass according to any one of claims 1 to 12, characterized in that: The thickness T of the chemically strengthened glass is ≤1 mm.
14. The chemically strengthened glass according to any one of claims 1 to 13, characterized in that: The Vickers hardness HV2 of the chemically strengthened glass satisfies: 500≤HV2≤900kgf / mm 2 .
15. The chemically strengthened glass according to any one of claims 1 to 14, characterized in that: In terms of mole percentage, the raw glass comprises the following components: SiO2: 45~59.5%, Al2O3: 9~30%, MgO: 7~30%, La2O3: 0~8%, ZrO2: 0~10%, ZnO: 0 to 5%, Li2O: 5.5 to 15%, Na2O: 1 to 5%, K2O: 2 to 5%.
16. The chemically strengthened glass according to claim 15, wherein: The ion exchange comprises at least one ion exchange treatment, each ion exchange treatment time is 0.3-10h, and each ion exchange temperature is 360-500°C.
17. The chemically strengthened glass according to any one of claims 1 to 16, characterized in that: The drop failure height of the chemically strengthened glass is greater than or equal to 1.1 m.
18. A method for predicting the drop failure height of chemically strengthened glass, characterized in that: The damage resistance characteristic value of the chemically strengthened glass according to any one of claims 1 to 17 Predicting the drop failure height H of the chemically strengthened glass, wherein H is related to Positive linear correlation.
19. A display screen, characterized in that: Comprising the chemically strengthened glass according to any one of claims 1 to 17.
20. A structural member, characterized in that: Comprising the chemically strengthened glass according to any one of claims 1 to 17.
21. An electronic device, characterized in that: It comprises the display screen as claimed in claim 19 or the structural member as claimed in claim 20.
Citation Information
Patent Citations
Chemically strengthened glass, and glass for chemical strengthening purposes
CN110546115A